(untitled) (Вестник КазНУ. Серия Востоковедения, 2016)
Мақалада Қытай кәсіпкерлерінің Қазақстан Респуб- ликасында айналысып жүрген қызметіне сипаттама бе- рілген, олардың негізгі кәсіпкерлік бағыттары, іс жүр- гізудегі ұлттық ерекшеліктері сарапталған. Қазақстан- дағы Қытай кәсіпкерлерінің негізгі мәселелері қарасты- рылған. In article attempt to present an overall picture of presence of Chinese businessmen in the Republic of Kazakhstan market becomes. Give the characteristic to specificity of business dealing of east partner. Fields of activity of Chinese businessmen in Kazakhstan are considered. Problems and prospects in development of Chinese business in Republic Kazakhstan are discussed.